Effect of Cyclic Heat Stress on Feeding-Related Hypothalamic Neuropeptides of Three Broiler Populations and Their Ancestor Jungle Fowl - Brugaletta, Giorgio; Greene, Elizabeth; Tabler, Travis; Orlowski, Sara; Sirri, Federico; Dridi, Sami (Frontiers in Physiology, 2021)
Heat stress (HS) has been increasingly jeopardizing the sustainability of the poultry production. Moreover, modern high-performing chickens are far less able to withstand HS than their predecessors due to higher growth rate and metabolic rates. Performance losses caused by HS are mainly ascribed to decreases in feed consumption. Since feed intake is tightly controlled by the hypothalamic centers of hunger and satiety, we sought to determine the effect of chronic cyclic HS on the expression of feeding-related hypothalamic neuropeptides (FRHN) in unselected chickens (i.e., the ancestor junglefowl – JF) and three broiler lines from diverse stages of genetic selection (i.e., the slow growing ACRB, the moderate growing 95RN, and the fast growing MRB). From 29 to 56 d, birds (n = 150 birds for each population) were subjected to either thermoneutral (TN, 25 ◦C) or cyclic heat stress (HS, 36◦C, 0900-1800 h) conditions. Molecular data were analyzed by two-way ANOVA with interaction between the main factors, namely environmental temperature and line. The expression of major FHRN, like neuropeptide Y, agouti-related peptide, proopiomelanocortin, and cocaine and amphetamine regulated transcript remained unchanged. However, melanocortin receptor 1 exhibited a line-dependent decreasing trend from JF to MRB under both TN and HS (p = 0.09), adiponectin expression showed a distinct trend toward significance with 95RB exhibiting the highest mRNA level irrespective of the environmental temperature (p = 0.08), and JF had a greater mRNA abundance of visfatin than ACRB under TN (p < 0.05). The hypothalamic integration of circadian information, acclimation to long-lasting HS exposure, stable hypothalamic pathways unaffected by evolution and genetic selection, focus on mRNA abundances, and use of the entire hypothalamus masking gene expression in specific hypothalamic nuclei are all possible explanations for the lack of variations observed in this study. In conclusion, this is the first assessment of the impacts of heat stress on feeding-related hypothalamic neuropeptides of chicken, with a valuable and informative comparison between the ancestor junglefowl and three differently performing broiler lines.